PUBLIC POLICY STRATEGY TO STIMULATE NATIONAL ECONOMIC GROWTH - Yaqin, Abdullah (International Conference on Humanity Education and Society (ICHES), 2025)
This study discusses public policy strategies in spurring inclusive and sustainable national economic growth amidst the dynamics of globalization and technological disruption. The research position emphasizes the importance of the role of governmentintervention through fiscal, monetary, sectoral, and digitalization policies to support economic growth while addressing social inequality. The method used is qualitative descriptive with a literature study approach to evaluate policy effectiveness andformulate evidence-based recommendations. The results of the study show that synergy between the central and regional governments, strengthening MSME innovation, and accelerating digital infrastructure development contribute significantly to increasing investment, exports, expanding employment opportunities, and macroeconomic stability. Policies that are designed strategically, integrated, and responsive are key to creating a national economic ecosystem that is fair, resilient, and adaptive to global change